Comparative Assessment of Pivotal Trials Supporting the Indication Approvals of Innovative and Modified New Anticancer Drugs in China, 2016–2022 - Lixia Fu; Ruifen Xue; Jie Chen; Guoshu Jia; Xiaocong Pang; Yimin Cui (Health Data Science)
Background: Since the launch of drug regulatory reform in 2015, China has substantially increased the availability of new cancer therapies. However, the efficacy evidence criteria for modified new anticancer drugs have not been evaluated. This cross-sectional study aimed to assess the pivotal trials supporting the indication approvals of innovative and modified new chemical anticancer drugs in China. Methods: The characteristics of indications, regulatory aspects, and pivotal trial designs were extracted and described. The primary efficacy endpoints of the pivotal clinical trials, including overall survival (OS) and progression-free survival (PFS), were quantitatively assessed by meta-analysis. Results: Between 2016 and 2022, 77 cancer therapeutics for 107 indications were approved in China based on 128 pivotal trials. Among the 107 indications, 64 (59.8%) were classified as innovative anticancer drugs, and 43 (40.2%) as modified new anticancer drugs. The study found that pivotal trials for innovative approvals tended to be single-arm trials, while modified approvals were more likely to employ randomized clinical trials with larger sample sizes and rigorous designs. Despite innovative drugs often receiving more expedited regulatory designations, there were no statistically significant differences in clinical benefit of OS or PFS outcomes between innovative and modified approvals. Conclusions: These results suggest that the current regulatory framework may prioritize the speed of approval for innovative drugs over the strength of supporting evidence. These findings align with the strategic trends of pharmaceutical companies and regulatory inclinations that aim to expedite the approval of innovative anticancer drugs with a high unmet need, thereby accelerating patients’ accessibility to treatment.